Corporations as actors of police militarization: the USA example - Pavlovic, Nikola (Sociološki pregled, 2026)
In modern globalized society, corporations have grown beyond the frameworks of traditional economic subjects and become key actors in economic, political, cultural and technological processes. Their economic power, often comparable to or even larger than the state budgets of many countries, apart from their great impact on global markets and capital flows, enables them to shape public policies through foundations and financial support to political structures. The defence sector, being extremely profitable, has been in the focus of corporations for decades. In technological terms, drones, armoured vehicles, semi-automatic and automatic weapons, mass surveillance systems are more often transferring from the military into the police sector. From the social aspect, military equipment and training entice a “war” mentality in police structures. Taking this into account, corporations have a huge impact on the process of police militarization, and this phenomenon is particularly evident in the USA. To prove this hypothesis, our research will apply a combined methodological approach which consists of the caste study method, content analysis method and critical-analytical method.
Keywords: police militarization; corporations; foundations; USA; security